The costs of epilepsy in Australia: A productivity-based analysis. (15th December 2020) - Foster, Emma; Chen, Zhibin; Zomer, Ella; Rychkova, Maria; Carney, Patrick; O'Brien, Terence J.; Liew, Danny; Jackson, Graeme D.; Kwan, Patrick; Ademi, Zanfina
Abstract : Objective: To determine the health economic burden of epilepsy for Australians of working age by using life table modeling and to model whether improved seizure control may result in substantial health economic benefits. Methods: Life table modeling was used for working age Australians aged 15–69 years with epilepsy and the cohort was followed until age 70 years. Published 2017 population and epilepsy-related data regarding epilepsy prevalence, mortality, and productivity were used. This model was then re-simulated, assuming the cohort no longer had epilepsy. Differences in outcomes between these cohorts were attributed to epilepsy. Scenarios were also simulated in which the proportion of seizure-free patients increased from baseline 70% up to 75% and 80%. Results: In 2017, Australians of working age with epilepsy followed until age 70 years were predicted to experience over 14, 000 excess deaths, more than 78, 000 years of life lost, and over 146, 000 productivity-adjusted life years lost due to epilepsy. This resulted in lost gross domestic product (GDP) of US $22.1 billion. Increasing seizure freedom by 5% and 10% would reduce health care costs, save years of life, and translate to US $2.6 billion and US $5.3 billion GDP retained for seizure freedom rates of 75% and 80%, respectively. Conclusions: Our study highlights the considerable societal and economic burden of epilepsy. Relatively modest improvements in overall seizure control could bring substantial economic benefits.